Interfacial Engineering of Van der Waals Coupled 2D Layered Materials. Issue 9 (15th February 2017) - Hong, Hao; Liu, Can; Cao, Ting; Jin, Chenhao; Wang, Shaoxin; Wang, Feng; Liu, Kaihui
Abstract : Engineering the properties of materials is of central importance in modern science and technology. In conventional bulk materials, the property changes are realized mainly through modifying the chemical bonds and crystalline structures, or introducing dopant atoms. Recent studies in van der Waals coupled 2D layered materials have demonstrated a different way of materials engineering through modifying interlayer interactions at the material interfaces, because the interlayer interactions in these materials can be easily controlled by changing interlayer stacking configurations and/or applying external fields. In this review, recent progresses in exploring the effects of van der Waals interlayer interactions on graphene, including the discovery of van Hove singularities, Fermi velocity renormalization, and Hofstadter's butterfly pattern, are discussed. Interlayer interactions at other 2D layered material interfaces, such as transition metal dichalcogenides and black phosphorus, are also discussed. Finally, the prospects of using the van der Waals coupled 2D layered materials for next‐generation electronics and optoelectronics are presented. Abstract : Interfacial engineering is an efficient way of materials engineering in van der Waals coupled 2D materials. This review discusses two main approaches, that is, designing interlayer stacking configurations and/or applying external field, to realize interfacial engineering. Potential applications in photonics and optoelectronics based on 2D layered materials are also presented.